La importancia de la prueba genética para demostrar el nexo entre víctima y víctimario, en los delitos sexuales en Colombia (2017)
The objective of the present investigation is to establish the importance of forensic genetics and the advance in the methods of detection of DNA to obtain the conclusive identification of the perpetrator in the commission of crimes against sexual freedom and in this way to establish a causal nexus between this one and the victim, which ultimately translates into an adequate administration of justice in Colombia. In order to achieve the above objective, we will carry out a historical parallel of those cases in which this means of proof was not applied and, consequently, erroneous conclusions were reached. Finally, we will point out that the effectiveness of the methods of DNA detection also depends on the rigorousness with which the auxiliary of justice applies the chain of custody and mitigates the risks of the alteration of its results